Stakeholders’ Perception Regarding the Internal Supervision Unit. A Case Study in Nusa Cendana University - Anaci Dethan, Minarni; Tunti, Maria; Bumi Kellen, Pius (Opción, 2019)
The aim of this study is to develop a common perception of Stakeholders regarding the Internal Supervision Unit. Internal Audit is a part of internal program control function which is responsible for independent reviewer practices of the organi- zation’s role and performance. A tertiary educational institution holds a strategic role in regards to higher educational purposes. Therefore, adequate management systems are required through internal audit. The object of this study is Nusa Cend- ana University Kupang NTT Province. Data were collected through questionnaire, interviews, and documentations. Data analysis employed SWOT analysis method. The Perceptions of Nusa Cendana University’s stakeholder regarding the Internal Supervision Unit lies within the1st quadrant which represents comparative advan- tage. The Internal Supervision Unit which is positioned in the connection of SO with a strength score of 3.52 and opportunity score of 2.66, precedes 1.85 points. These points to a SO strategy which emphasizes on using strengths and identi- fied opportunities in order to enhance the performances of the Internal Supervision Unit. This in turn is expected to shift the bureaucracy paradigm in Nusa Cendana University, which will give an opportunity for the Internal Supervision Unit to de- velop significantly. The conclusions of this study are: 1)Stakeholders’ perception has recognized change from negative views of the Internal Supervision Unit which sees them as watchdogs ;a mere executive extension and “problem seeker”, to a more positive view which sees the control unit as a consulting peer. 2) The pres- ence of the Internal Supervision Unit can prevent fraud, 3) The Internal Supervi- sion Unit work set up by strong legal basis 4) The Internal auditors carry out their duties fully based on regulations and procedures.